2013
DOI: 10.1051/0004-6361/201220648
|View full text |Cite
|
Sign up to set email alerts
|

Star forming regions in a sample of HST spiral galaxies

Abstract: Aims. The presence of small-and large-scale star formation structures in a sample of six spiral Hubble Space Telescope (HST) galaxies is investigated to identify small structures of young stars known as OB associations and to tell whether they are formed inside larger scale star forming stellar structures in a hierarchical form. Methods. This process was based on a friend-of-friend (FOF) algorithm applied to the bright, early type stars above a certain color cutoff limit in order to ensure that we include main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
(51 reference statements)
0
6
1
Order By: Relevance
“…On the other hand, a wider range of sizes were found by Battinelli et al (2000), who studied the young stellar groups in the galaxies NGC 2717, NGC 1058, and UGC 12732; these authors found values for the radius mode between 25 and 50 pc and between 52 and 89 pc for the mean radius. Battinelli (1991) derived a mean radius of 45 pc for the OB associations in the SMC, this value is larger than the value found by Drazinos et al (2016) for the same galaxy. In our Galaxy, Melnik & Efremov (1995) found still lower values for the OB association sizes in the solar vicinity with a mode value of 15 pc and an average radius of 20 pc.…”
Section: Parameters Of the Plc Groupscontrasting
confidence: 57%
See 2 more Smart Citations
“…On the other hand, a wider range of sizes were found by Battinelli et al (2000), who studied the young stellar groups in the galaxies NGC 2717, NGC 1058, and UGC 12732; these authors found values for the radius mode between 25 and 50 pc and between 52 and 89 pc for the mean radius. Battinelli (1991) derived a mean radius of 45 pc for the OB associations in the SMC, this value is larger than the value found by Drazinos et al (2016) for the same galaxy. In our Galaxy, Melnik & Efremov (1995) found still lower values for the OB association sizes in the solar vicinity with a mode value of 15 pc and an average radius of 20 pc.…”
Section: Parameters Of the Plc Groupscontrasting
confidence: 57%
“…In the literature lower values were found too. For example, Drazinos et al (2016) estimated a mean radius of ∼30-35 pc for the young associations in four Local Group galaxies (SMC, M31, M33, and NGC 6822) using a friend-of-friend algorithm. Drazinos et al (2013) found a mean size between 62 and 75 pc (radius of ∼31-38 pc) for the associations in the galaxies NGC 925, NGC 2541, NGC 3351, NGC 3621, NGC 4548, and NGC 5457.…”
Section: Parameters Of the Plc Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence the constructed surveys include small systems within larger ones, revealing the hierarchical pattern in their structure (see Table 1 for details). Drazinos et al (2013) in their study of six local galaxies apply a friends-of-friends algorithm (see Huchra & Geller, 1982, for the original implementation of the method) on stellar catalogs within given search radii, set by the expected dimensions for associations, aggregates, complexes, and supercomplexes. Gouliermis et al (2010Gouliermis et al ( , 2015a) apply a contour-based cluster analysis for the detection of asymmetric stellar concentrations on surface stellar densities produced with star counts.…”
Section: Stellar Complexesmentioning
confidence: 99%
“…The first algorithm that we employed for star cluster identification was Friend of Friend (FoF). The code used was developed by P. Drazinos (Drazinos et al 2013) and searches for pairs of objects that are closer than a cut off distance limit. The main aim of the method is to apply an objective criterion to the stellar structure identification process.…”
Section: Identification Of Star Clusters In the Smcmentioning
confidence: 99%